Oral anticoagulants and risk of dementia: A systematic review and meta-analysis of observational studies and randomized controlled trials. (January 2019) - Mongkhon, Pajaree; Naser, Abdallah Y.; Fanning, Laura; Tse, Gary; Lau, Wallis C.Y.; Wong, Ian C.K.; Kongkaew, Chuenjid
Highlights: Use of Oral anticoagulants (OACs) is associated with reduced risk of dementia. Maximizing time in therapeutic range could improve cognitive function in warfarin users. OACs are useful not only for stroke prevention, but also for protection against dementia. Methodological issues and the small number of studies limit the evidence. Abstract: Atrial fibrillation (AF) is a documented risk factor for dementia. However, it is unclear whether oral anticoagulant (OAC) treatment can reduce the development of dementia or cognitive impairment. We conducted a systematic review and meta-analysis of the association between OAC use and subsequent dementia development in AF patients by searching databases from their inception to February 2018 without language restriction. Six studies (one randomized controlled trial and five observational studies) met the inclusion criteria. The pooled adjusted risk ratios (RRs) suggested a protective effect of OAC use in reducing dementia risk (RR 0.79 [95% CI: 0.67 – 0.93], I 2  = 59.7%; P  = 0.005). Further, high percentage of time in therapeutic range (TTR) was associated with a decreased risk of dementia (RR 0.38 [95% CI 0.22-0.64], I 2  = 81.8%; P  < 0.001). Our results support the hypothesis that AF-related dementia may be due to silent brain infarcts and micro-embolism that could be prevented by OAC use. Future studies with prospective follow-up with direct comparison of vitamin K antagonists and direct oral anticoagulants are needed.